Isolation and identification of a novel human parechovirus - Ito, Miyabi; Yamashita, Teruo; Tsuzuki, Hideaki; Takeda, Naokazu; Sakae, Kenji (Journal of general virology, 2004)
1 Department of Microbiology, Aichi Prefectural Institute of Public Health, Nagare 7-6, Tsuji-machi, Kita-ku, Nagoya, Aichi 462-8576, Japan 2 Department of Virology II, National Institute of Infectious Disease, Tokyo, Japan Correspondence Miyabi Ito itorymiatcrest.ocn.ne.jp A cytopathic agent (A308/99) was isolated using Vero cells from a stool specimen of a 1-year-old patient with transient paralysis. The agent was approximately 28 nm in diameter with a distinct ultrastructure resembling the virus particle of an enterovirus. It could not be neutralized by antisera against human picornaviruses such as human enterovirus, Aichi virus or human parechovirus. The virion contained three capsid proteins with molecular masses of 38, 30·3 and 30 kDa. Determination of the complete nucleotide sequence of A308/99 revealed that the nucleotide and deduced amino acid sequences were closely related to those of human parechoviruses. When 11 regions encoding the structural and non-structural proteins were compared, A308/99 had between 75 and 97 % and 73 and 97 % nucleotide identity with human parechovirus type 1 (HPeV-1) and type 2 (HPeV-2), respectively. The most distinctive divergence was seen in VP1, which had 74·5 % and 73·1 % nucleotide identity with HPeV-1 and HPeV-2, respectively. Viruses related to A308/99 were also isolated from three patients with gastroenteritis, exanthema or respiratory illnesses. A308/99 and these other three isolates had no arginineglycineaspartic acid (RGD) motif, which is located near the C terminus of VP1 in HPeV-1 and HPeV-2. A seroepidemiological study revealed that the prevalence of A308/99 antibodies was low (15 %) among infants but became higher with age, reaching more than 80 % by 30 years of age. These observations indicate that A308/99 is genetically close to, but serologically and genetically distinct from, HPeV-1 and HPeV-2 and accordingly can be classified as third serotype of human parechovirus. The complete nucleotide sequence of the A308/99 strain has been deposited in DDBJ, EMBL and GenBank under accession no. AB084913 . The GenBank accession nos of A317/99, A354/99, A628/99, A1086/99, A942/99 and A10987 /00 reported in this paper are AB112482 AB112487 .